Comparación del peso de diferentes tipos de plumas entre cinco especies de aves del páramo de Chirripó, Costa Rica - Barrantes, Gilbert (Universidad de Costa Rica, 1993)
Plumage weight was compared in highland and wide-range bird species (N= 18 weight samples): Sooty Robín (Tutdus nigresce/lS). Rufous-collared Sparrow (Zonotrichia cape/lSís), Volcano Junco (íunco vulcani), Slaty Flowerpiercer (Diglossa plumbea), and Volcano Hummingbird (Selasphorus flammula) caplured al the Chirripó Paramo (August 1986). Relative plumage weight was not clearly related with body weight for any feather type. The relative plumage weighl was higher ín the higland species.